2023
DOI: 10.5114/pm.2023.126345
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening in Jordan; a review of the past and an outlook to the  future – facts and figures

Abstract: Introduction: This study aims to assess the attitude, knowledge, and behaviour of Jordanian women toward cervical cancer screening and its phenomenal role in preventing the disease, and to identify the defects and obstacles in the national screening programs for early detection of this manageable kind of malignancy.Material and methods: A prospective study via a questionnaire that included the demographic data, knowledge, behaviour, and attitude among Jordanian women about the cervical screening program using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, screening has been an effective method for reduction of mortality rates in the Jordan region. In recent years, a study was conducted and reported that 53% of women were not being screened in Jordan [11]. Furthermore, the qualitative studies with review-based investigations relevant to cervical cancer screening concluded that the significant barriers to efficient screening included the higher service cost, fear of cancer diagnosis, discourtesy of healthcare staff for patients, the scarcity of privacy and comfort at healthcare centres, and a lack of available and accessible healthcare quality services in Jordan and developed countries [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, screening has been an effective method for reduction of mortality rates in the Jordan region. In recent years, a study was conducted and reported that 53% of women were not being screened in Jordan [11]. Furthermore, the qualitative studies with review-based investigations relevant to cervical cancer screening concluded that the significant barriers to efficient screening included the higher service cost, fear of cancer diagnosis, discourtesy of healthcare staff for patients, the scarcity of privacy and comfort at healthcare centres, and a lack of available and accessible healthcare quality services in Jordan and developed countries [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many countries worldwide have successfully implemented long-term and sustained screening programs for common gynecological diseases, yielding signi cant results. [5][6][7][8] In high-income countries like the United States, cervical and breast cancer mortality rates have declined in recent years due to widespread screening programs. These programs facilitate early detection, diagnosis, and treatment, providing women with increased opportunities to access high-quality gynecological care.…”
mentioning
confidence: 99%